DEVELOPMENT OF HUMAN RESOURCE MANAGEMENT IN ISLAMIC EDUCATIONAL INSTITUTIONS - Faizah Andriani, Nurdiana; Rindanigsih, Ida (Antis Publisher, 2024)
Quality Human Resource (HR) is the main component that must be considered. Human Resources must continue to be developed and be able to keep up with the times. Today's technological sophistication requires everyone involved in educational institutions to be ready to transform in order to achieve school progress and personal quality. To analyze more deeply, research was conducted using the library research method. This research method is an activity of collecting library data with literacy, reading, recording, and interpreting into research data. This method is done by making literature or previous research as the main data source. Human resource development in educational institutions must involve all elements involved in the organization. The process of developing human resources in educational institutions must be adjusted to the needs analysis and complex planning so that it can support the process of achieving the goals of educational institutions. a well-structured and systematic process can produce quality and competent human resources. Namely qualified teaching and educational staff.